MODUL PRAKTIKUM JARINGAN EIGRP - Mulyadharma Weking, Marcus; Sudiarta, Pande Ketut; Ardana, I Putu (Jurnal SPEKTRUM; Vol 8 No 1 (2021): Jurnal SPEKTRUM, 2021)
Writing a thesis report with the title EIGRP Network Practicum Module aims to increase the knowledge and skills of Udayana University Electrical Engineering students, especially those who concentrate on Telecommunication Engineering and Multimedia Networks in managing the EIGRP network and this thesis is also the requirements for graduation from the final level of undergraduate or S1 lectures. The lack of learning media related to this protocol makes it difficult for students to understand how the EIGRP dynamic route protocol works. It is important to learn the EIGRP dynamic route protocol because it is useful in managing building-scale network routes and between buildings. The EIGRP experiments carried out in the practicum module are divided into several variations with the general purpose of understanding how the EIGRP protocol works, configurations, and variables. This practicum also contains how EIGRP works using metrics as a benchmark in determining the best possible route along with analyzing metrics using mathematical equations. The EIGRP network practicum module has been tested on 10 practitioners who are selected students on the condition that these students have studied and mastered network fundamentals and routing concepts in the Telecommunication Network Engineering course. Practical activities in the sequence are working on preliminary reports, pretests, practical module experiments, final reports, questionnaires, and post-tests. In general terms, this practicum module is deemed capable of increasing the understanding of the practitioner regarding the EIGRP protocol. The work stages in this practicum module are easy to understand and follow by the practitioner. 7 out of 10 practitioners strongly agree if the EIGRP network practicum module applied to the Telecommunication Network Practicum Course.